Cryoballoon Ablation for Pulmonary Vein Isolation in Patients With Persistent Atrial Fibrillation: One-Year Outcome Using Second Generation Cryoballoon. (October 2015) - Koektuerk, Buelent; Yorgun, Hikmet; Hengeoez, Oezlem; Turan, Cem H.; Dahmen, Alina; Yang, Alexander; Bansmann, Paul M.; Gorr, Eduard; Hoppe, Christian; Turan, Ramazan G.; Horlitz, Marc
Abstract : Background—: Data regarding the freedom from atrial fibrillation (AF) in the follow-up of persistent AF patients is limited. The second-generation cryoballoon has better cooling properties compared with first-generation cryoballon. In this study, we aimed to assess the medium-term efficacy of second-generation cryoballoon in patients with persistent AF. Methods and Results—: A total of 100 patients (63±10 years, 80% male) with symptomatic persistent AF, despite ≥1 antiarrhythmic drug(s), who were scheduled for pulmonary vein isolation using second-generation cryoballoon were enrolled in this study. Follow-up was based on outpatient clinic visits, including Holter ECGs. Recurrence was defined as a symptomatic or documented arrhythmia episode of >30 seconds excluding a 3-month blanking period. As a result, 393 pulmonary veins (7 patients with common ostium) were successfully isolated. Mean procedural and fluoroscopy times were 96.2±21.3 and 19.7±6.7 minutes, respectively. Phrenic nerve palsy occurred in 3% (3/100) of the patients. At a mean follow-up duration of 10.6±6.3 months, 67% of the patients were in sinus rhythm. Stepwise multivariable Cox proportional hazard regression analysis showed that early AF recurrence (hazard ratio 3.83, 95% confidence interval 1.91–7.68, P <0.001) was the only independent predictor for late AF recurrence apart from other clinical and echocardiographic variables. Conclusions—: Our findings indicated that second-generation cryoballoon use is associated with favorable outcomes in patients with persistent AF. Recurrence at blanking period was the only predictor of long-term AF recurrence.